The role of technology and institutions for growth: Danish creameries in the late nineteenth century - Ingrid Henriksen; Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2011)
We consider the relative contributions of changing technology and institutions for economic growth through the investigation of a natural experiment in history: the almost simultaneous introduction of the automatic cream separator and the cooperative ownership form in the Danish dairy industry from around 1880. Using a new database of statistics from creameries and the tool of stochastic frontier analysis, we find that both institutions and technology were important for the success of the Danish dairy industry and, by implication, the growth and early development of the Danish economy.
Keywords: L2; N5; O3; Q1; 330; Creameries; dairies; Denmark; development; economic growth; institutions; technology; stochastic frontier analysis